2011
DOI: 10.4137/cmrt.s5102
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin and Its Application in the Treatment of Multidrug-Resistant Enterobacteriaceae Infections

Abstract: Abstract:The use of fosfomycin has been limited in therapeutics in recent years. Because it has shown good antibacterial activity in vitro and clinical efficacy in some domains, it has been proposed as an alternative to current antimicrobial agents, which are subject to increasing resistance. This paper reviews the main properties of fosfomycin and the latest publications concerning multidrugresistant Enterobacteriaceae infections. In uncomplicated urinary tract infections, a single oral dose was found to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 177 publications
0
3
0
Order By: Relevance
“…This is evident also from our study: since the majority of infections were caused by MDR gram negative bacteria, fosfomycin was intravenously administered in combination regimens associated mostly with carbapenems, cephalosporins and tigecycline. Therefore, the actual use of fosfomycin goes beyond the treatment of urinary tract infections, being expanded to the treatment of bacteremias especially in severe settings, including critically ill patients [12,20,31]. The wide variety of fosfomycin dosages employed in our study was chosen considering PK/PD parameters, namely renal function and pathogen MIC (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is evident also from our study: since the majority of infections were caused by MDR gram negative bacteria, fosfomycin was intravenously administered in combination regimens associated mostly with carbapenems, cephalosporins and tigecycline. Therefore, the actual use of fosfomycin goes beyond the treatment of urinary tract infections, being expanded to the treatment of bacteremias especially in severe settings, including critically ill patients [12,20,31]. The wide variety of fosfomycin dosages employed in our study was chosen considering PK/PD parameters, namely renal function and pathogen MIC (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable interpatient variability in the plasma concentrations of fosfomycin has been demonstrated in critically ill patients [16][17], posing this population at risk of over-or under-drug dosing [18][19]. Indeed, it has been shown that older age and impaired renal function result in lower kidney elimination and high plasma fosfomycin concentrations [20][21]. However, these factors explain only a part of the observed pharmacokinetic variability.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the starting material ( SI-1 ) will be used to synthesize the bioavailable version of fosfomycin, commercially known as fosfomycin trometamol ( SI-2 ) (Figure ). This structure contains an ether linkage. It has been shown that the presence of this functional group improves biodegradation performance .…”
Section: Introductionmentioning
confidence: 99%